Art institutions of Western Ukraine: From self-creation to system creation - Babii, Nadiia; Hubal, Bohdan; Prystai, Halyna; Chmelyk, Iryna; Lototska, Vita (Research Journal in Advanced Humanities, 2023)
The study highlights the dominant strategies and specific practices of self-organization of artists in the cities of Western Ukraine for the representation of current art at the end of the 20th and beginning of the 21st centuries. “Grassroots” institutions that are not related to traditional models of national institutions, but began to emerge simultaneously with the development of capitalist relations in the 1990s and supported mainly performative practices are considered. The result of their activity was, among other things, the activation of the process of forming an alternative aesthetic taste of the artistic audience and society. The issues of self-organized institutions are considered in the context of a specific temporal perspective, where they are considered not as spaces, but as potential processes that appear under the condition of a specific temporal rearrangement of contents. In this context, the transition from group initiatives to individual projects involved in the formation of the current “cultural” capital of Western Ukrainian cities is analyzed.